Nine-year bird community development on Radovesická spoil heap - Korejs, Kryštof (Jihočeská univerzita, 2022)
Despite being valuable indicators of habitat change, birds are rarely used in restoration science. We surveyed birds on a large North-Bohemian spoil heap in 2012 and in 2019-21. We analysed bird community response to nine-year site development, human land use, primary vegetation productivity and proportion of senescent vegetation, vegetation age and structure, and restoration approach. Our findings offer an original insight into how birds respond to habitat characteristics, and highlight the importance of birds as indicators of restoration success.
Nine-year bird community development on Radovesická spoil heap
Keywords: Spoil heap; Vegetation structure; NDVI; PSRI; bird community; landscape restoration; Spoil heap; Vegetation structure; NDVI; PSRI; bird community; landscape restoration